Model for Work-Life Balance: Integrating Theory and Research - Joshi, Pusp Raj (SP Swag: Sudur Paschim Wisdom of Academic Gentry Journal, 2024)
Purpose: This paper aims to integrate the concept, theories, and factors affecting work-life balance based on previous research, and propose a conceptual model for further studies. Methods: The paper conducted a comprehensive review of the existing literature on work-life balance using a review matrix to analyze and synthesize the findings of various research. Results: The literature review revealed several methods and components of work-life balance, including family-friendly policies, work-life conflict, and the role of work and life. The paper synthesized these findings and proposed a conceptual model for further study. Value: This paper contributes to the existing literature on work-life balance by integrating the concept, theories, and factors affecting work-life balance. The proposed conceptual model can serve as a foundation for future research in this area. The findings of this study have implications for organizational policy and practice, highlighting the importance of work-life balance in promoting employee well-being and productivity. DOI: https://doi.org/10.69476/sdpr.2024.v01i01.002